Formation and development of the Acquis Communautaire in France, Germany and Switzerland: A comparative legal analysis - N. O. Rastorhuieva (Law and Safety)
The article is devoted to the comparative legal analysis of the formation and development of the acquis communautaire in France, Germany and Switzerland with a view to identifying similarities and differences in the formation and development of the acquis communautaire in countries with different legal status in the European Union. The analysis was carried out using comparative legal, formal legal, dialectical, historical and legal, hermeneutical and other methods, as well as the principles of determinism, pluralism of opinions and complexity of knowledge. On the basis of and through the disclosure of the concept of “acquis communautaire”, the diversity of its understanding within different approaches and the nature of this phenomenon, as well as the study of the formation of the acquis communautaire specifics, it is established that this process took place in the course of formation of the European Communities in the 1950s with the participation of France and Germany on the basis of a combination of liberal market and general social values, and its development took place during the elaboration of the foundations of the mechanism for adoption of a common European policy.